Financial Report Training: Financial Management Education for Gampong Jantho Makmur MSMEs - Utami, Sorayanti; Kusuma, T. Meldi; Rahmawati, Syarifah; Tabrani, Mirza; Effendi, Rustam; Anis, Nasrillah; Sabrina, Nadira; Syach, Saidina Attalarik; Akbar, M Fathan (Universitas Syiah Kuala, 2024)
Preparing financial reports is essential in developing Micro, Small and Medium Enterprises (MSMEs), apart from increasing the number of business actors and making a significant contribution to the economy. This service activity was conducted in Gampong Jantho Makmur, Jantho District, Aceh Besar Regency. This service aims to assist community MSMEs in preparing financial reports to make it easier for the community to manage their finances and have an impact on business development. Implementing this service uses education and counselling methods regarding preparing simple financial reports. The material presented includes the benefits of using financial reports and distributing invoice books to MSMEs. The service results are that business actors feel immensely helped and positively influenced by the financial management of MSMEs in Gampong Jantho Makmur. It is recommended that the community of MSME players continue to consistently manage financial reports by using bookkeeping for more organized financial arrangements.